Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2017)
Until the 1950s, most black men in Montreal worked for the railway companies as sleeping car porters, dining car employees, and red caps. The city’s English-speaking black community took root in Little Burgundy because it was close to Windsor and Bonaventure train stations. The area between Saint-Henri and Griffintown, north of the Lachine Canal, in the city’s Southwest Borough, was once known by many names. “Little Burgundy” was invented in the 1960s by city officials to describe their urban renewal plans for the area. If employment mobility was foundational in making this community, it proved just as central in its unmaking in the 1960s and 1970s. The shift from trains to cars and trucks had a two-fold impact on Little Burgundy. First, employment levels collapsed with the decline of passenger train travel, leaving many black men unemployed. Then the state built a highway through the neighbourhood to facilitate the mobility of mainly white suburban workers and consumers making their way to the central city. Next, the neighbourhood was “renewed” on a massive scale. What followed were years of dislocation and crisis. Much of the black community was dispersed as a result. It was no coincidence. The radical restructuring of North American cities disproportionately affected racialized minorities and poor whites. What was different here was that the area’s reputation for being the birthplace of black Montreal emerged after the community had been largely dispersed by urban renewal.